Recovery of photoexcited magnetic ordering in Sr2IrO4. (9th April 2019) - Li, Jiemin; Wang, Ruitang; Guo, Haizhong; Zhu, Yi; Cao, Yue; Liu, Jian; Ding, Hong; Wen, Haidan; Liu, X
Abstract: The recovery of antiferromagnetic and lattice order of Sr2 IrO4 upon laser excitation was measured by time-resolved x-ray diffraction on nanosecond time scales. The in situ measurements of both magnetic and lattice order parameters allow direct comparison of their time evolutions without ambiguity. We found that the magnetic order recovers with two time constants. The fast sub-nanosecond recovery is associated with the re-establishment of three dimensional antiferromagnetic order while the slow sub-nanosecond recovery agrees with the lattice cooling on tens of nanoseconds. The strong oscillating behavior of magnetic order during the long time recovery may be related to complicated dynamics of defect-pinned magnetic domains.